Detection of Deoxyribonucleic Acid Damage Induced by Metal Ion Interactions and Repair of Metal Ion Deoxyribonucleic Acid Cross-links - Esau, Neal (My University, 2010)
There are many forms of DNA damage. One of these, DNA-metal cross-links are particularly problematic as they not only affect the tautomeric structure of DNA, but can also inhibit enzymatic activity and block amplification with DNA polymerases. Since the inability to amplify DNA can affect many fields of genetic research, it is necessary to find ways to identify this damage and repair the DNA. Copper is one metal that can form metal-DNA cross-links and can seriously affect the recovery and analysis of degraded DNA from forensic or archaeological material. In this research DNA-copper cross-links were generated for the development of a repair method and applied to an archaeological sample. The DNA-copper adducts were identified through the use of gas chromatography-mass spectrometry on several templates of different complexity: single deoxyribonucleotides, a synthetic 22 base pair double stranded DNA fragment, modern amplified DNA, and an ancient extract with naturally occurring copper cross-links. A number of chemicals were considered for direct reversal repair of copper-DNA cross- links of which ethylenediamine was successful. Treatment of all the templates with ethylenediamine resulted in the repair of the nucleobase, specifically guanine which is the most susceptible to copper cross-link formation. The success of the direct reversal repair was verified using GC-MS based on expected retention time and the identification of ion fingerprints. The amount of copper-DNA adducts measured in each template varied greatly as did the success of the direct reversal repair although repair was evident in all samples.
Keywords: Detection of Deoxyribonucleic Acid Damage Induced by Metal Ion Interactions and Repair of Metal Ion Deoxyribonucleic Acid Cross-links